2017
DOI: 10.1111/jne.12542
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in brain aromatase activity in the female quail brain following expression of sexual behaviour

Abstract: In male quail, oestrogens produced in the brain (neuro-oestrogens) exert a dual action on male sexual behaviour: they increase sexual motivation within minutes via mechanisms activated at the membrane but facilitate sexual performance by slower, presumably nuclear-initiated, mechanisms. Recent work indicates that neuro-oestrogens are also implicated in the control of female sexual motivation despite the presence of high circulating concentrations of oestrogens of ovarian origin. Interestingly, aromatase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It should be noted that the measurements of estrogens do not correlate with aromatase activity in most cases and future work should tackle this discrepancy (Charlier et al, 2011b ; Dickens et al, 2014 ; de Bournonville et al, 2017b ). Interestingly, central aromatase is not only important for male sexual behavior but was also shown recently to be involved in female sexual behavior in Japanese quail (de Bournonville et al, 2016 , 2017a ), see also recent discussion in Cornil ( 2017 ). The very high concentration of aromatase in birds make them a very suitable model to investigate its function in modulating sexual behavior but it is likely that rapid change in aromatase activity are also important in mammals and fish, as rapid effects of estrogens were demonstrated on sexual motivation in rat and Goldfish (Cross and Roselli, 1999 ).…”
Section: Role Of Steroids In the Brains Of Fish Mammals And Birdsmentioning
confidence: 93%
“…It should be noted that the measurements of estrogens do not correlate with aromatase activity in most cases and future work should tackle this discrepancy (Charlier et al, 2011b ; Dickens et al, 2014 ; de Bournonville et al, 2017b ). Interestingly, central aromatase is not only important for male sexual behavior but was also shown recently to be involved in female sexual behavior in Japanese quail (de Bournonville et al, 2016 , 2017a ), see also recent discussion in Cornil ( 2017 ). The very high concentration of aromatase in birds make them a very suitable model to investigate its function in modulating sexual behavior but it is likely that rapid change in aromatase activity are also important in mammals and fish, as rapid effects of estrogens were demonstrated on sexual motivation in rat and Goldfish (Cross and Roselli, 1999 ).…”
Section: Role Of Steroids In the Brains Of Fish Mammals And Birdsmentioning
confidence: 93%
“…Aromatase activity is up-regulated in the POM and down-regulated in the tuberal hypothalamus of females within minutes of acute restraint stress (Fig.3a) (Dickens et al 2011; Dickens et al 2012). By contrast, an interaction with a sexually active male results in a decreased activity in the POM (de Bournonville et al 2017b). Importantly, aromatase activity positively correlates with tissue content in estradiol in both the POA and the MBH, regardless of whether females had been stressed or paired with a male partner (Fig.…”
Section: Brain Aromatase Is Regulated In a Similar Fashion In Femalesmentioning
confidence: 99%
“…Interestingly, telencephalic aromatase activity is rapidly regulated by phosphorylating conditions in zebra finches, particularly within synaptosomes (Comito et al, 2016;Cornil et al, 2012). A line of work in Japanese quail has shown that aromatase activity is also sensitive to environmental stimulation (sex interaction or stress) in both males and females (Cornil et al, 2005;de Bournonville et al, 2013de Bournonville et al, , 2017Dickens et al, 2011Dickens et al, , 2014. These effects occur within very short time scales (2-5 min).…”
Section: Sex Differences and Similaritiesmentioning
confidence: 99%
“…Neuroestrogens are important neuromodulators that regulate social communication and other sexual behaviors (Balthazart et al, 2018;Cornil & de Bournonville, 2018;de Bournonville et al, 2017;Vahaba & Remage-Healey, 2018). The production and local action of neuroestrogens is key for auditory processing in songbirds.…”
Section: Introductionmentioning
confidence: 99%